2012
DOI: 10.1108/10595421211229664
|View full text |Cite
|
Sign up to set email alerts
|

Branding: perceptual effects on consumer evaluations

Abstract: PurposeThe purpose of this study is to determine the extent that extrinsic product attributes (brand name/packaging) influence consumers' perceptions and resulting evaluation of intrinsic product attributes, quality, and purchase intention.Design/methodology/approachA 2 (brand) x 2 (treatment group) experimental “taste‐test” design was created using two brands of cookies (national versus store brand) and two treatment conditions (whether the cookie was in its respective package or placed in the competitor's pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
0
7
0
3
Order By: Relevance
“…Estos resultados se encuentran alineados con los supuestos de Breneiser y Allen (2011), Field et al (2012) y Wang (2013) que defienden que la calidad percibida y la generación de las preferencias están influidas por los atributos extrínsecos del producto. Por otro lado, para los dos productos de alimentación testados, las calificaciones de la aceptación general son mayores en las catas informadas que en las catas ciegas, especialmente en el caso de las marcas Hacendado y Carrefour.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Estos resultados se encuentran alineados con los supuestos de Breneiser y Allen (2011), Field et al (2012) y Wang (2013) que defienden que la calidad percibida y la generación de las preferencias están influidas por los atributos extrínsecos del producto. Por otro lado, para los dos productos de alimentación testados, las calificaciones de la aceptación general son mayores en las catas informadas que en las catas ciegas, especialmente en el caso de las marcas Hacendado y Carrefour.…”
Section: Resultsunclassified
“…El estudio de Breneiser y Allen (2011) sobre la influencia de la marca en la preferencia del sabor de una bebida de cola demuestra que los consumidores en la cata informada, conocedores de la marca de lo que están probando, prefieren la bebida de marca Coca-Cola. Lo mismo confirman Field et al (2012), sobre el efecto de la marca en la evaluación de atributos intrínsecos, al comprobar que las galletas marca Chips Ahoy obtienen valoraciones más altas cuando se dan a probar en su envase original que cuando se muestran en el envase de una marca de distribuidor. Por el contrario, las galletas tipo Chips Ahoy de marca de distribuidor obtienen mejores resultados cuando se dan a probar dentro del envase original de las galletas Chips Ahoy.…”
Section: La Valoración De Los Atributos Extrínsecosunclassified
See 1 more Smart Citation
“…Aaker conceptualized brand equity as perceived quality, brand loyalty, brand awareness, brand associations (Aaker D. , 1996). Brand Awareness is the possibility of brand name come to mind without making an effort (Field, Bergiel, Giesen , & Field, 2012). Brand associations are everything that connects the customer to the brand, including mental images, product features, brand personality, and symbols (Cottler & Pfoertsch, 2006).…”
Section: Brand Equity and Brand Preferencementioning
confidence: 99%
“…Brand equity could facilitate in the effectiveness of brand extensions and brand introductions and this is because consumers who trust and display loyalty towards a brand are willing to attempt to adopt brand extensions. Field et al (2012) determined the extent that extrinsic product attributes (brand name/packaging) impact consumers' perceptions and resulting evaluation of intrinsic product attributes, quality, and purchase intention. They reported that store brand managers must increase the quality of their product if they expect to capture market share from the national brands.…”
Section: Introductionmentioning
confidence: 99%